Mobilités socio-spatiales et production territoriale en Sénégambie - Mohamadou Mountaga Diallo (EchoGéo)
This article aims to study the role of the border in fashioning daily activity territories. A major geographical discontinuity, the border is traditionally defined as the limit of a state territory, and a symbol of its sovereignty. The Senegal-Gambia border performs this function, and creates numerous border effects that are exploited by the population. Social actors and merchants in the Senegal-Gambia border areas, through their daily mobility around the border, connect places on both sides of that border. In so doing, they produce distinct territories, experiences and spaces. The border is a link that joins and binds together shared spaces and strong communal solidarity. But these border territories are also subject to competition and even to conflict relating to local actors involved in various border cooperation initiatives. The strengthening or formalization of these local initiatives involves part of the ongoing decentralization process in Senegal and Gambia, and also reflects recent progress made by ECOWAS in the formalization of border cooperation. This could, however, be hampered by differences of interest and by tensions between the two states.